1985
DOI: 10.1063/1.96284
|View full text |Cite
|
Sign up to set email alerts
|

Donor neutralization in GaAs(Si) by atomic hydrogen

Abstract: Hydrogen plasma exposure of n-type GaAs(Si) at 250 °C results in a decrease of the free-carrier concentration by several orders of magnitude. This neutralization effect has been demonstrated in silicon-doped layers grown by molecular beam epitaxy or formed by annealed implants as well as in bulk material. The same effect is produced electrochemically (H3PO4 electrolyte), whereas helium plasma exposure has no effect, thus confirming the role of hydrogen insertion. The hydrogen penetration depth into GaAs(Si) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
1
4

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(52 citation statements)
references
References 17 publications
2
45
1
4
Order By: Relevance
“…As such, hydrogen can also interact strongly with chemical impurities within the lattice. 10,11 Initial evaluation of deuterium tagging of defects in epitaxial MCT films grown by molecular-beam epitaxy on a 19% lattice-mismatched Si(211) substrate was done using secondary-ion mass spectrometry (SIMS) to determine the deuterium profiles. SIMS profiles are shown in Fig.…”
Section: Evaluation Of Awmmentioning
confidence: 99%
“…As such, hydrogen can also interact strongly with chemical impurities within the lattice. 10,11 Initial evaluation of deuterium tagging of defects in epitaxial MCT films grown by molecular-beam epitaxy on a 19% lattice-mismatched Si(211) substrate was done using secondary-ion mass spectrometry (SIMS) to determine the deuterium profiles. SIMS profiles are shown in Fig.…”
Section: Evaluation Of Awmmentioning
confidence: 99%
“…In such devices, hot electron degradation due to the breaking of SiH bonds and to the formation of dangling bonds is observed and recently, it has been shown [1] that the reduction of this degradation and the improvement of the device lifetime could be achieved by incorporating deuterium rather than hydrogen. For Si-doped GaAs materials and devices, the ability of hydrogen to passivate the electrically active shallow impurities and as a consequence to form an electrically neutral SiH complex is well known [2]. So, it is of interest to study the influence of hot electrons on the stability of complexes and the related isotope effects.…”
Section: Introductionmentioning
confidence: 99%
“…Chevallier et al [58] demonstrated donor passivation in GaAs before it was known that donors could be passivated in Si. Subsequently, all of the important donor dopants in GaAs have been shown to be passivated by H2 plasma exposure [59].…”
Section: Donor-h Complexesmentioning
confidence: 99%